Social Learning and Regenerative Sustainability: Unlocking value created in sustainability projects in higher education - Royle, Carlene (Rhodes University, Faculty of Education, Department of Education)
This qualitative study considers two bodies of theory, regenerative sustainability and social learning theory, within a tertiary education context. Universities offer unique opportunities, across both the formal and informal curriculum, that engage with the two-fold socioeconomic and environmental crises. The study explores both the promise of unlocking value in an ex-linear economy; and the healing and regenerative benefits in moving toward greener practices. Through an embedded case study at Rhodes University, in the Eastern Cape of South Africa, this research explores the value that is being unlocked in campus-based sustainability projects, when considered through a social learning lens (Lave and Wenger, 1991). Invitations to participate in this study were extended to project-leads of sustainability initiatives originating from Rhodes University campus. Six projects, which have been active on campus in recent years, were selected and, through semi-structured interviews, the insights of 12 participants were captured and analysed using the associated Value Creation Framework (VCF) developed by Wenger, Trayner and De Laat (Wenger, Trayner, de Laat, 2011) and later Wenger-Trayner and Wenger Trayner (2014, 2015, 2020). The VCF consists of value cycles that interconnect dynamically, including Orientating, Strategic, Enabling, Immediate, Potential, Applied, Realised and Reframed or Transformative value cycles. The study identified instances of all these value cycles, within and across the six embedded case studies (project). Drawing on social learning theorists the analysis further focused on instances of collaboration, agency and boundary crossing. Additional themes that emerged across the majority of the embedded study projects, were a convergence of socio and eco; a whole-systems perspective shared by project leads; the importance of the social commons; language as an enabler; and problem solving for system change. A recommendation is proposed to further unlock the unbounded value created through such projects by reframing the informal curriculum opportunities offered on university campuses as social learning spaces where students can practice agency. To do so, would require formalizing various forms of system support, thus facilitating expanded learning in regenerative sustainability activities, for the common social and planetary good.
Keywords: Social learning -- South Africa -- Makhanda; Sustainability -- South Africa -- Makhanda; Education, Higher Social aspects -- South Africa -- Makhanda; Social accounting -- South Africa -- Makhanda; Education, Higher Activity programs -- South Africa -- Makhanda; Value creation; Agent (Philosophy); Sustainable Development Goals